SISTEM INFORMASI MANAJEMEN KEMITRAAN PT. JAPFA PADA BIDANG PETERNAKAN AYAM BROILER BERBASIS ANDROID - Rijal, Muhammad; Marlina, Marlina; Yunus, Mughaffir; Masnur, Masnur (JURNAL ILMIAH INFORMATIKA, 2025)
This study aims to evaluate the implementation of PT. Japfa's Partnership Management Information System based on Android in supporting operational efficiency and enhancing partnership transparency in broiler chicken farming. The research focuses on three main variables: ease of use of the application, security and reliability of the application, and the benefits of the application for farmers. Using a quantitative approach with a descriptive design, data were collected through questionnaires distributed to 30 farmers partnered with PT. Japfa, and in-depth interviews were conducted to gather further insights into user experiences.The findings indicate that the application facilitates the management of farm operational data through an intuitive interface, and automation features that enhance financial reporting efficiency. However, some farmers requested more intensive training on how to use the application. In terms of security and reliability, the application successfully protects sensitive data and handles system errors effectively, though routine updates are still needed to improve security. Additionally, the application provides significant benefits in terms of partnership transparency, accelerating harvest reporting, and organizing feedstock management more effectively.This research contributes valuable insights into the development of technology-based applications for the livestock sector, particularly in information-based partnership management. Recommendations for future research include enhancing poultry health monitoring features and integrating data more comprehensively to support more efficient management.